2001
DOI: 10.1080/073993301300003108
|View full text |Cite
|
Sign up to set email alerts
|

Older Women With Breast Cancer: New Understandings Through Grounded Theory Research

Abstract: Breast cancer incidence increases by decade of life, significantly affecting the lives and well-being of older women. In a critical analysis of three decades of quantitative and qualitative research literature. I found an indication that something changed over the course of time that allowed women to adjust to breast cancer and resolve emotional turmoil. However, it was not clear what was "adjusted," or what constituted the process that allowed women to restore meaning within illness. In this paper I discuss t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 24 publications
1
27
1
Order By: Relevance
“…The women in this study reported a number of physical problems which pre-existed their breast cancer but, in common with the study by Crooks (Crooks 2001), there seemed to be little discussion of these with the women prior to surgery or through rehabilitation. The findings also suggest that older women may sometimes have difficulty distinguishing between the effects of breast cancer or breast cancer treatment and the effects of other co-morbidities, particularly arthritis, which may have implications for the detection of recurrent disease.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…The women in this study reported a number of physical problems which pre-existed their breast cancer but, in common with the study by Crooks (Crooks 2001), there seemed to be little discussion of these with the women prior to surgery or through rehabilitation. The findings also suggest that older women may sometimes have difficulty distinguishing between the effects of breast cancer or breast cancer treatment and the effects of other co-morbidities, particularly arthritis, which may have implications for the detection of recurrent disease.…”
Section: Discussionmentioning
confidence: 55%
“…As a consequence the number of older women in the population living with the long-term consequences of breast cancer is also increasing as women survive longer and as the population continues to age. Although there is a growing body of research into living with breast cancer (Crooks 2001;Liang, Burnett et al 2002;Ballantyne 2004;Maly, Leake et al 2004) the experiences of older women have been relatively neglected.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations